HIV/sexual and reproductive health program for HIV prevention: The youth-adult partnership with schools approach - Fongkaew W. (2014)
The aim of the present study was to describe the development and evaluation of a program designed to prevent HIV/AIDS. A participatory action research (PAR) approach was used in collaboration with ten schools in Chiang Mai Province, Thailand, to develop a youth- adult partnership with schools (YAPS) model. The YAPS model included curricula using participatory learning experiences, edutainment approaches, and skills building strategies for enhancing youth leaders' capacities. Results showed that the YAPS model was effective in leadership role preparation and in empowering youth leaders to undertake activities on their own, initiate creativity and share knowledge on sexuality education and HIV prevention messages with students in schools. The use of partnerships and the participatory process mobilized parents, teachers, and school administrators to play a proactive role in sexuality education and HIV prevention for early adolescents in schools, resulting in the integration of the program into the school system.